Programa de estimulación en habilidades para la vida en población Indígena del municipio Coyaima - Tolima (2023)
Life Skills (HpV) is a concept that the World Health Organization (WHO) proposed in 1993. These skills are incorporated into each individual through habitual responses and behaviors, formed during the acquisition of knowledge, the development of abilities and adaptation to society